Minorities, social capital and voting - Pieter Bevelander; Ravi Pendakur (Institute for the Study of Labor (IZA), 2007)
It is widely held that voter turnout among immigrants and ethnic minorities is lower than among the native born. The goal of our paper is to explore the determinants of voting, comparing immigrant, minority and majority citizens in Canada. We use the 2002 wave of the Equality Security Community Survey to explore the relationship between personal characteristics (age, sex, education, and household type) work characteristics, social capital attributes (trust in government, belonging, civic awareness and interaction with others) and ethnic characteristics (ethnic origin, place of birth and religion) and voting. We find that the combination of socio-demographic and social capital attributes largely overrides the impact of immigration and ethnicity. This suggests that it is not the minority attribute that impacts voting. Rather it is age, level of schooling and level of civic engagement which effects voting, both federal and provincial.
Keywords: 330; Wahlverhalten; Bürgerbeteiligung; Social Capital; Humankapital; Ethnische Gruppe; Kanada